Low Health Literacy (LHL): A Conniving Opponent of Patient Treatment Compliance - Abdul Kader Mohiuddin (Budapest International Research and Critics University, 2023)
In order to access, comprehend, and use information to make decisions about their health, people must possess certain personal traits and social resources, which are referred to as health literacy. Patients' ability to engage in complex disease management and self-care is strongly related to their level of health literacy. It can help us stay healthy by preventing illness and effectively managing existing illnesses. Personal health literacy refers to a person's ability to locate, comprehend, and apply information and services to support health-related decisions and actions for themselves and others. The World Health Organization recommends health literacy as a tool for achieving several key targets outlined in the Sustainable Development Goals. Low health literacy (LHL) is most commonly associated with mature patients with chronic health conditions who have limited education and are not necessarily from a lower income group. Furthermore, being literate in general does not imply being literate in health.